Potensi Hipertoleransi Calopogonium mucunoides, Centrosema pubescens dan Cajanus cajan yang Tumbuh pada Limbah Penambangan Emas Terkontaminasi Sianida dan Merkuri - Syarif, Fauzia; Hidayati, Nuril; Juhaeti, Titi (JURNAL BIOLOGI INDONESIA, 2007)
ABSTRACTPotency of Hypertolerance of Calopogonium mucunoides, Centrosema pubescensand Cajanus cajan . Grown on Gold Mine waste Media Contaminated by Cyanideand Mercury. Cleaning up contaminated environment by using green technology ofphytoremediation is urgently needed in the future. These plants will be utilized ashyperaccumulators for cleaning up the contaminated sites. The results of plant screeningshowed that some plant species, which grow in the contaminated areas, indicated hightolerance and potentially effective in accumulating cyanide and mercury in their rootsand above ground portions. Those plants are Calopogonium mucunoides and Centrosemapubescens. This research aims to examine the potency of three candidate plants i.eCalopogonium mucunoides, Centrosemapubescens and Cajanus cajan, that were grownunder three different media i.e tailing waste of PT ANTAM contaminated by cyanide,public mine or PET1 waste that were contaminated by mercury and non contaminated topsoil as a control. The results showed that all of the species were able to grow undercontaminated media and showed a considerable tolerance by indicated high cyanide andmercury accumulation in their shoot and root. Among those three plants, Centrosemapubescens showed the highest level of cyanide and mercury accumulation i.e 3.29 mg I- CN (in the shoot), 34.72 mg I- Hg (in the shoot) and 17.47 mg lk Hg (in the root),followed by Calopogonium mucunoides i.e 14,97 mg I- CN (in the root). Concentrationratio of CN and Hg accumulation in shoot/root of Centrosemapubescens was >I indicatingthat this plant, according to the definition can beconsidered as a hyperaccumulator.Key Words: Calopogonium mucunoides, Centrosemapubescens, Cajanus cajan, mercury,cyanide, waste